2010
DOI: 10.1007/s00431-010-1190-y
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit hyperactive disorder in school-aged children in Saudi Arabia

Abstract: The current study was designed to explore the prevalence of attention-deficit hyperactive disorder (ADHD) in primary schools in Saudi Arabia. The study collected data from both teachers and parents for 708 primary school pupils attending grades 1-3 (7-9 years old), using DSM-IV criteria of ADHD. The result showed that the overall rate of ADHD was 2.7%, and in particular, the rate of attention types, 2.0%; hyperactive/impulsivity type, 1.4% and combined type, 0.7%. Teachers reported ADHD in a higher frequency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 19 publications
6
33
1
8
Order By: Relevance
“…One outcome study with two years follow-up revealed that infants rarely continue to have gratification phenomena beyond the age of two years 7 . Four of our children (21%) developed features suggestive of ADHD, which is much higher than the prevalence figures in our region that do not exceed 6% of normal pre-school children 16,17 . These infants tended to be younger of age at onset and had higher attack frequency.…”
Section: Discussioncontrasting
confidence: 71%
“…One outcome study with two years follow-up revealed that infants rarely continue to have gratification phenomena beyond the age of two years 7 . Four of our children (21%) developed features suggestive of ADHD, which is much higher than the prevalence figures in our region that do not exceed 6% of normal pre-school children 16,17 . These infants tended to be younger of age at onset and had higher attack frequency.…”
Section: Discussioncontrasting
confidence: 71%
“…Prevalence varies from country to country. In Nigeria, for instance, the latest prevalence is 3.2% [6], while in other African countries, such as South Africa, Democratic Republic of Congo, and Ethiopia, the reported prevalence varies from 5.4% to 8.7% [7]. The reported prevalence from other continents follows a similar trend.…”
Section: Introductionmentioning
confidence: 93%
“…1 The prevalence of ADHD in children in the west has been reported as being between 2% and 5.5%. 1,2 In Saudi Arabia, there have been studies that have placed the prevalence of ADHD at being between 2.7% and 4.2% on average, 3 with reports of incidence as high as 7% in male students. [3][4][5] It is generally accepted that the prevalence of ADHD reduces with age with the typical adult rates being between 1.2% and 2.7%.…”
Section: Introductionmentioning
confidence: 99%